Drilling performance of nano-diamond bonded SiC composite abrasives for CFRP laminates by dual-axis grinding wheel system. (3rd May 2021) - Kunimine, Takahiro; Kurachi, Kazumasa; Tsuge, Hideaki; Yamada, Motoko; Sato, Hisashi; Watanabe, Yoshimi
Abstract : The design and fabrication of nano-diamond (ND) bonded silicon carbide (SiC) composite material were conducted as an attempt to obtain better drilling performance of SiC abrasives. The ND/SiC composite abrasives were fabricated by mechanical bonding of the NDs on the surface of SiC abrasives with the use of dry particle composing machine together with amorphous silica as a bond material. A comparative study on drilling performance for carbon fiber-reinforced plastic (CFRP) laminates by the SiC abrasives and ND/SiC composite abrasives was performed with dual-axis grinding wheel system. Hole-qualities such as roundness and roughness were improved by using the ND/SiC composite abrasives. Enhanced drilling performance of the ND/SiC composite abrasives was also obtained in terms of feed rate dependence of the thrust force. The ND/SiC composite abrasives could make holes with lower thrust force at higher feed rate, compared with the SiC abrasives due to the enhanced self-dressing effect together with the original drilling performance of the ND abrasive as synergetic effect caused by interfacial design between the ND/SiC composite abrasives and metal matrix in the grinding wheels. These results indicate the new controlling method of holding force of abrasive grains in metal bonded grinding wheel.